2019
DOI: 10.1093/annonc/mdz017
|View full text |Cite
|
Sign up to set email alerts
|

Sperm count in Swedish clinical stage I testicular cancer patients following adjuvant treatment

Abstract: Background: Little is known regarding sperm production following adjuvant treatment in testicular cancer (TC) clinical stage I (CS I) patients.Patients and methods: A total of 182 TC patients aged 18-50 years were prospectively included during 2001-2006 at any given time within 5 years of orchiectomy. Semen samples were delivered postorchiectomy but before further treatment, 6, 12, 24, 36 and 60 months (T 0 -T 60 ) after completed therapy. Total sperm number (TSN) and sperm concentration (SC) were used as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…Weibring et al . 38 reported similar observations, but further noted that semen quality improves 12 months after the end of treatment. Di Bisceglie et al .…”
Section: Discussionsupporting
confidence: 58%
“…Weibring et al . 38 reported similar observations, but further noted that semen quality improves 12 months after the end of treatment. Di Bisceglie et al .…”
Section: Discussionsupporting
confidence: 58%
“…A prospective study of clinical stage 1 TC patients showed that adjuvant chemotherapy was not associated with a long-term effect on sperm concentration. 23 The mean sperm concentrations at 12 months after completion of treatment were 43 million/mL in the surveillance group, 33 million/mL in the one cycle of carboplatin group and 31 million/mL in the one cycle of BEP group.…”
Section: Discussionmentioning
confidence: 89%
“…Mediastinal germinoma was the most common type of EGCT in our unit, which included 1 teratoma, 6 non-teratoma and 3 unspecified. There are two subtypes of TGCT, namely, seminoma and non-seminoma ( 19 , 20 ). Seminomas are the most usually diagnosed type of testicular cancer, accounting for approximately half of all cases ( 19 , 21 ).…”
Section: Resultsmentioning
confidence: 99%